2005
DOI: 10.1590/s0036-36342005000300002
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile of dengue hemorrhagic fever cases in Mexico

Abstract: Objective. Dengue hemorrhagic fever is a public health problem in Mexico since 1994. With four serotypes circulating the risk of epidemic dengue hemorrhagic fever is increasing. Material and Methods. We describe the clinical features of confirmed cases in the social security health system (IMSS) from 1995 to 2003. Clinical picture and epidemiological features were compared and a multivariate model was fitted to evaluate associations. Results. Cases were divided into two groups: 438 patients with dengue fever, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 18 publications
1
17
0
2
Order By: Relevance
“…The percentage of DENV-4 isolates was less than 1% in 2009 and 2010 [26]. For the period 1995–2003, Navarette-Espinosa et al reported that 9% of isolates were DENV-1, 60% were DENV-2, and 31% were DENV-3 (there were no DENV-4 isolates) [33].…”
Section: Resultsmentioning
confidence: 99%
“…The percentage of DENV-4 isolates was less than 1% in 2009 and 2010 [26]. For the period 1995–2003, Navarette-Espinosa et al reported that 9% of isolates were DENV-1, 60% were DENV-2, and 31% were DENV-3 (there were no DENV-4 isolates) [33].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, regarding the clinical behavior, dengue is characterized by the presence of fever, headache, myalgia, arthralgia of variable intensity, and exanthema; this is accompanied by general malaise and other signs and symptoms that may or may not be present [15]- [17]. Characteristically, mild-intensity presentations are indistinguishable in many infectious diseases, and only severe cases of dengue may manifest differently through hemorrhages, capillary fragility data, or leak of liquids.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 82% of Vietnamese children in shock were correctly identified using the narrow WHO classification system 50 , although the tourniquet test had a sensitivity of only 41.6% 51 . Differences between disease patterns from Southeast Asia and the Americas can be traced to clinical practice, particularly to the failure of clinicians in the Americas to collect appropriate data to fulfil the requirements of the WHO case definition 52 . In Asia, better case management and intensive national programs to educate parents and medical staff improved early care and avoidance of over hydration of dengue hemorrhagic fever/dengue shock syndrome patients 43 .…”
Section: Health Services Determinants Clinical Profilementioning
confidence: 99%